Aspects of social identity, self concept, self esteem, self functioning and gender aspects (part 10) - Yahaya, Azizi (2012)
A social identity consists of the social or public aspects of yourself, the impression that you typically create in others. Many of your more visible characteristics-such as gender, ethnicity and occupation-contribute to your identity and also go into the formation of identity.